اتجاهات العلماء في قضية التصوير: دراسة مقارنة في ضوء السنة النبوية - Muhammad Akmalludin bin Mohd Hamdan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research is concerned with the issues encircling photography while aiming to understand the islamic scholars' bearings on the aforementioned subject and the reasons underpinning their differences likewise. The divergence of opinions between scholars since the early era until today substantiates the significance of this particular research. The discourse that first revolved around the concern on the crafting of sculptures and statues began to include several other related matters, particularly those that recently emerged in this modern age, such as photography and others. Principally, three distinct approaches were relied upon in conducting this research: the inductive method, analytical method and comparative method. For the first method, the researcher started by searching and collecting related hadith and extracted them through the common hadith extraction principles. The second approach was utilized to analyse the contradiction of opinions between scholars and the reasons for the differences, as well as to criticize the chain of the narrators and the text of the hadith with an explanation on the status of the narrations. On the other hand, the final method was used by the researcher in comparing the position of the scholars in this particular matter, with some academic appraisals on their respective stance. The researcher came to the conclusion that the divergence of the scholars in this matter is not grounded by the status of the hadith; authentic, weak or fabricated. Yet, the contradiction is because of their differences in understanding the hadith and the reasoning method underwent by them. This difference in understanding of the hadith is, likewise, based upon several other reasons, mentioned in this thesis.